2008
DOI: 10.1165/rcmb.2008-0059oc
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Peptide Recognition and Immune Activation Facilitated by Human Peptide Transporter PEPT2

Abstract: Microbial detection requires the recognition of pathogen-associated molecular patterns (PAMPs) by pattern recognition receptors (PRRs) that are distributed on the cell surface and within the cytosol. The nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) family functions as an intracellular PRR that triggers the innate immune response. The mechanism by which PAMPs enter the cytosol to interact with NLRs, particularly muropeptides derived from the bacterial proteoglycan cell wall, is poorly und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 24 publications
(24 reference statements)
2
36
0
Order By: Relevance
“…This hypothesis is supported by the fact that SLC15A1 was identified as an MDP transporter in Caco-2/bbe epithelial cells (40), but found to be dispensable for mediating MDP entry in macrophages (39). Similarly, SLC15A2 has been shown to trigger transport of the Nod1 ligand iE-DAP in human upper airway epithelial cells (41), but was found to be dispensable in our assays. Finally, it must be noted that the knockdown of SLC15A4 expression in HEK293T cells did not result in a complete ablation of NF-B activation induced by Nod1 ligands.…”
Section: Discussionsupporting
confidence: 65%
“…This hypothesis is supported by the fact that SLC15A1 was identified as an MDP transporter in Caco-2/bbe epithelial cells (40), but found to be dispensable for mediating MDP entry in macrophages (39). Similarly, SLC15A2 has been shown to trigger transport of the Nod1 ligand iE-DAP in human upper airway epithelial cells (41), but was found to be dispensable in our assays. Finally, it must be noted that the knockdown of SLC15A4 expression in HEK293T cells did not result in a complete ablation of NF-B activation induced by Nod1 ligands.…”
Section: Discussionsupporting
confidence: 65%
“…PEPT2 is a protondependent transporter of di-and tri-peptides. PEPT2 transports intracellularly bacterial peptides that are recognized by the nucleotide-binding oligomerization domain (NOD)-like receptor that results in activation of the innate immune system [59]. PEPT2 appears to have a role in immune activation of macrophages by the transport of S-nitrosothiols intracellularly [60].…”
Section: Results: Disproportionate Molecular Targets Identified By Damentioning
confidence: 99%
“…SLC15A2 (also known as peptide transporter 2), a close homolog of SLC15A1, shows more fastidious ligand selectivity. Swaan et al (2008) used computational modeling to calculate the SLC15A2 pharmacophore and predicted that only ie-DAP and not MDP would be imported. Using primary epithelial airway cells and transfected Chinese hamster ovary cells they confirmed these predictions and demonstrated that the affinity constant for ie-DAP uptake was approximately 200 mM.…”
Section: Activation and Signal Transduction In The Nucleotide-bindmentioning
confidence: 99%